Glomus Tumor in the Tracheal Region: Case Report - Souza, Leonardo Rodrigues Fusco de (Brazilian Journal of Case Reports, 2024)
This report presents a rare case of a glomus tumor in the mediastinal trachea. A 53-year-old man with tracheal stenosis underwent invasive procedures until the discovery of a benign tracheal lesion in the form of a glomus tumor. Diagnosis was made through bronchoscopy and chest tomography, and the patient was treated surgically with bronchoscopy and cryoablation. After recurrence, a mediastinal tracheoplasty was performed. In addition to the rarity of this type of tracheal lesion, we found it important to report this case, as remembering glomus tumor in benign lesions may assist the medical community involved in treating this condition in making the correct therapeutic decisions for this surgical pathology.